William Inge and the subversion of gender : rewriting stereotypes in the plays, novels, and screenplays - Johnson, Jeff (Jefferson, N.C. : McFarland & Co., 2005)
"This study of Inge's work focuses particularly on his technique of "gendermandering," patterns of gender-role reversals which Inge exploits not only for dramatic effect but also to subvert social expectations. The author concentrates on material that is strictly Inge's, not adaptations or collaborations, and on work that has been published and is readily available to the general public"--Provided by publisher.
Stereotypes, gender roles and gendermandering -- The critics -- Major works: Come back, Little Sheba; Picnic; Bus stop; The dark at the top of the stairs; Splendor in the grass -- Minor works: A loss of roses; Natural affection; Where's daddy?; Good luck, Miss Wyckoff -- Short plays.
Includes bibliographical references (p. 185-188) and index.
Keywords: Gender identity in literature; Sex role in literature